Bangladesh : Poverty Reduction Strategy Paper--Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2012)
Bangladesh's second Poverty Reduction Strategy Paper -- 'Steps Towards Change: National Strategy for Accelerated Poverty Reduction II (NSAPR II)' - provides a framework for implementing the government's agenda during FY09-FY11. First prepared by a Caretaker government,1 the NSAPR II was later revised by the current elected government to reflect its priorities. The NSAPR II outlines five strategic priorities and describes the supporting strategies to achieve them. This Joint Staff Advisory Note (JSAN) provides feedback on priority areas for strengthening the NSAPR II and its implementation.